2023
DOI: 10.3390/min13010123
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Gaseous SO2 Attack on Sandstone in the Yungang Grottoes

Abstract: The Yungang Grottoes, with over 1500 years of history, have been subjected to air pollution since the last century. Field investigations have indicated that acid gases, particularly sulfur dioxide (SO2), have accumulated on the surface of the sculptures and caused various types of decay that reduce their artistic value. To shed new light on the gas–stone interaction process, artificially accelerated weathering was performed on local sandstone in the laboratory. In a specially developed test device, fresh speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In these rocks, calcium is released from minerals, such as plagioclase, if they undergo weathering, such as acid leaching. In some cases, the lack of a significant intrinsic calcium and sulfur source for the formation of the gypsum crusts suggests an external source of calcium ions, e.g., pollution, mortars, and neighboring carbonate stones [45][46][47][48][49]. Other authors suggested that Ca 2+ may come from the hydrolysis processes of plagioclase mineral grains under acid environments [50].…”
Section: Structure and Main Componentsmentioning
confidence: 99%
“…In these rocks, calcium is released from minerals, such as plagioclase, if they undergo weathering, such as acid leaching. In some cases, the lack of a significant intrinsic calcium and sulfur source for the formation of the gypsum crusts suggests an external source of calcium ions, e.g., pollution, mortars, and neighboring carbonate stones [45][46][47][48][49]. Other authors suggested that Ca 2+ may come from the hydrolysis processes of plagioclase mineral grains under acid environments [50].…”
Section: Structure and Main Componentsmentioning
confidence: 99%